Effect of Negative Pressure Wound Therapy for Soft Tissue Injuries of Foot and Ankle in Patients at a Tertiary Care Hospital - Khursheed, Roqayyah Munawwer; Akhlaq Ali Khan, Faisal; Ali, Hyder; Zahid, Zaara; Kiran, Saba; Ullah Ansari, Muhammad Kamran (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the effect of Negative Pressure Wound Therapy (NPWT) in patients with foot and/or ankle injury compared with conventional dressing techniques.Study Design: Randomized controlled trial (Trial No: NCT04569305).Place and Duration of Study: Department of Plastic Surgery, Dr Ruth K.M. Pfau Civil Hospital, Karachi Pakistan, from Dec 2019 to Oct 2020.Methodology: All patients with foot and ankle injury resulting in soft tissue injury with or without bones and tendons exposed were included. Thirty-five patients were randomized into the NPTW-Group and 35 into the Conventional Treatment Group using the lottery method. NPTW was applied to an injured foot and ankle area after debridement and cleaning the necrosed tissue. The effect of the technique was assessed by measuring the wound surface area covered with healthy granulation tissue measured in a centimetre square on follow-up.Results: Mean wound grade at the start of treatment was estimated as 3.20±0.71 in the NPWT-Group and 3.14±0.73 in the Control-Group, and at the end of treatment as 1.20±0.53 in the NPWT-Group and 1.71±0.78 in the Control Group. The mean wound size at the start of treatment was estimated as 52.74±21.92 cm2 in the NPWT-Group and 54.08±23.28 cm2 in Controls.At the end of treatment, an average wound size was estimated as 21.61±13.46 in NPTW and 30.40±16.50 in controls. NPTW significantly reduced wound grade and size more effectively than the conventional technique (p